Pendampingan Pengelolaan Kualitas Air dan Pemasaran Berbasis Web dan Marketplace Bagi Pembudidaya Ikan Kabupaten Magelang: Assistance Activities for Water Quality Management and Web-Based Marketing and Marketplace for Fish Farmers in Magelang Regency - Hertika, Asus Maizar Suryanto; Amron, Kasyful; Shofwan, Shofwan; Lal, Mohammad Tamrin Bin Mohamad; Putra, Renanda Baghaz Dzulhamdhani Surya; Alfarisi, Muhammad Asnin; Mukhlis, Dharu Habib; Eryanto, Erik; Savira, Riza; Al Farida, Soraya Alifa Ni Mah; Halimah, Marsa Fatin; Wijanata, Ida Bagus Pascad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Water quality management and effective marketing strategies are two important aspects of fish farming, especially in Magelang Regency which has great potential in the freshwater fisheries sector. However, many farmers still face obstacles in water quality management and product marketing limited to the local market. This community service activity aims to provide solutions through training in water quality mitigation and management, as well as web-based marketing and marketplace assistance for fish farmers in Magelang. The methods applied include technical education on water quality parameters such as dissolved oxygen, pH, nitrate, and ammonia, as well as assistance in utilizing digital platforms to expand market access. The results of the activity showed a significant increase in the understanding and ability of farmers to manage water quality, which has a positive impact on fish health and productivity. In addition, the implementation of digital marketing strategies has succeeded in expanding market reach and increasing farmer income. With this approach, it is hoped that this empowerment model can be adopted by farmers in other areas, supporting sustainable local economic growth.